The effect of realistic mathematics education (RME) on the improvement of students’ spatial ability in solid geometry - Indah Ameliya Fitriani; Warsito Warsito; Ratu Sarah Fauziah Iskandar; Iden Rainal Ihsan (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to examine the effect of the Realistic Mathematics Education (RME) approach on students’ spatial ability in learning solid geometry and to identify the improvement in students’ spatial ability after its implementation. RME needs empirical evidence on how contextual tools and digital integration sustain long-term spatial ability. The research employed a mixed-methods approach with a Sequential Explanatory design, consisting of two stages: quantitative and qualitative. The population included all seventh-grade students totaling 98 students, while the sample comprised 65 students divided into an experimental class (33 students) and a control class (32 students). Data were collected using tests and interviews. The test instrument consisted of 10 essay questions that were valid and reliable. The independent samples t-test showed a significant difference (p = 0.022), and the N-Gain score (0.68) indicated a moderate improvement, with significance values of 0.058 for the experimental class and 0.200 for the control class, and were homogeneous with a significance value of 0.929. Qualitative findings from interviews indicated an improvement in students’ spatial ability in solid geometry. Overall, the results demonstrate that the RME approach has a positive effect and contributes to the improvement of students’ spatial ability. The findings confirm that the RME approach significantly enhances students’ spatial ability in solid geometry, demonstrating both statistically significant differences and meaningful learning gains compared to conventional instruction. This study contributes empirical evidence on the effectiveness of integrating contextual and representational learning within RME to systematically develop students’ spatial ability in geometry learning contexts.